MicroRNA expression profiling of the fifth-instar posterior silk gland of Bombyx mori - Li, Jisheng (BioMed Central, 2014)
BACKGROUND: The growth and development of the posterior silk gland and the biosynthesis of the silk core protein at the fifth larval instar stage of Bombyx mori are of paramount importance for silk production. RESULTS: Here, aided by next-generation sequencing and microarry assay, we profile 1,229 microRNAs (miRNAs), including 728 novel miRNAs and 110 miRNA/miRNA* duplexes, of the posterior silk gland at the fifth larval instar. Target gene prediction yields 14,222 unique target genes from 1,195 miRNAs. Functional categorization classifies the targets into complex pathways that include both cellular and metabolic processes, especially protein synthesis and processing. CONCLUSION: The enrichment of target genes in the ribosome-related pathway indicates that miRNAs may directly regulate translation. Our findings pave a way for further functional elucidation of these miRNAs and their targets in silk production. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/1471-2164-15-410) contains supplementary material, which is available to authorized users.